UMPSA explores aviation with Delta Aerospace Sdn. Bhd. - Naqiah, Puaad (UMPSA, 2024)
SUBANG, 13 September 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is expanding its cooperation in the field of aviation with industry partners through the signing of a Memorandum of Understanding (MoU) with Delta Aerospace Sdn. Bhd. recently.